Chemical element contents and speciations in bottom sediments from the Transpacific profile - Zinaida V Pushkina; M I Stepanets; E V Cherkasova (PANGAEA, 1977)
The paper deals with regularities of distribution of iron, manganese, copper, nickel, and vanadium in interstitial waters from different lithofacies types of bottom sediments on the profile from the coast of Mexico to the Wake Atoll in the Pacific Ocean. With increasing distance from the shore and with transition from reduced coastal sediments to oxidized deep-sea red clays concentration of iron and manganese in the interstitial waters greatly decreases. Elevated concentration of dissolved iron (0.34 mg/l) was observed only in highly reduced terrigenous sediments from the shelf and continental slope of Mexico. The highest concentrations of manganese (13.2 mg/l) were measured in hemipelagic carbonate-siliceous-clayey sediments. Compared to Pacific seawater interstitial waters are enriched in Fe, Mn, Cu, Ni, V. Interstitial waters contain only from 0.000004 to 1.2% of total contents of these elements in bottom sediments.
Supplement to: Pushkina, ZV et al. (1977): Iron, manganese, copper, nickel, and vanadium in interstitial waters from sediments of the Northeast Pacific. Litologiya i Poleznyye Iskopaemyye (Lithology and Mineral Resources), 12(3), 3-16